Bagaimana Asia-Pacific Economic Cooperation (APEC) Menyesuaikan Harapan dan Menjawab Tantangan untuk Mencapai Berbagai Tujuannya? - Pakpahan, Beginda (UI Scholars Hub, 2014)
APEC has been established since 1989 with 21 member countries. The crucial questions are what are major works of APEC from 1994 to present time? What are APEC's current challenges? And, how APEC manages its hopes and responds to the challenges in order to reach its goals? This article argues that APEC is on the right track to attain the Bogor goals by pursuing trade liberalization in its member countries. There are several works which have been achieved by APEC, for example: its achievements for trade liberalization in goods and its support for facilitating foreign investment in the Asia-Pacific region. However, there are several challenges for APEC, such as the complexity of regional cooperation in South-East and East Asia and the social implications for vulnerable groups in developing countries within APEC as negative impacts of trade liberalization. Consequently, APEC should manage its hopes and responds challenges in order to meet its goals. APEC must adjust its hopes to be matched with the latest political and economic developments in the Asia-Pacific region. At the same time, South-East and East Asia become more integrated economic regions and apply an open regionalism for other countries from outside of these regions to engage with the developments in these regions. Overall, APEC must respond to crucial challenges (e.g. geo-politics and geo-economics) in the Asia-Pacific region which have changed overtime.